1974
DOI: 10.1051/lait:197453824
|View full text |Cite
|
Sign up to set email alerts
|

Etude des composés neutres volatils présents dans le Camembert

Abstract: II.-MATERIEL ET METHODES a) Les fromages Les échantillons numérotés de 1 à 11 ont été achetés dans le commerce. Il s'agissait d'échantillons de Camembert normand à

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Neither of these two compounds have been identified in cheeses, but Dumont et al (1974b) have found similar compounds, methylcyclopentane and methylpentane, in Camembert. The biosynthetic pathways of these compounds are not known.…”
Section: Discussionmentioning
confidence: 94%
“…Neither of these two compounds have been identified in cheeses, but Dumont et al (1974b) have found similar compounds, methylcyclopentane and methylpentane, in Camembert. The biosynthetic pathways of these compounds are not known.…”
Section: Discussionmentioning
confidence: 94%
“…In the surface mold-ripened cheeses, ketones are detected from the first week of ripening (Dolezalek and Brabcova, 1964;Moinas et al, 1973;Dumont et al, 1974c), and according to Dolezalek and Brabcova (1964), they were absent in the very mature cheeses. This observation agrees with the findings of Moinas et al (1973) where butan-2-one and pentan-2-one were identified only in young Camembert cheese and their concentration decreased to nondetectable levels during ripening.…”
Section: Neutral Compoundsmentioning
confidence: 99%
“…This observation agrees with the findings of Moinas et al (1973) where butan-2-one and pentan-2-one were identified only in young Camembert cheese and their concentration decreased to nondetectable levels during ripening. Dumont et al (1974c) reported that methyl ketones with an even carbon number, except butan-2-one, are never present in large amounts in Camembert, except in very ripe cheeses; conversely nonan-2-one, heptan-2-one, and undecan-2-one quantities steadily increase during ripening of Camembert. Dartey and Kinsella (1971) observed that the concentration of methyl ketones in Blue cheese increases up to day 70 of ripening and then decreases.…”
Section: Neutral Compoundsmentioning
confidence: 99%
“…Specifically, indole, skatole, p-cresol, and p-hydroxylphenylacetic acid have been reported to contribute to putrid, fecal or unclean aroma fiavors in cheese (Schormüller, 1968;Dumont et al, 1974;Guthrie, 1993). The metabolic pathways involved in the formation of these compounds have been described in a number of microorganisms; however, these pathways have not been described in lactic acid bacteria.…”
Section: Introductionmentioning
confidence: 99%